Assessment of decomposition method for linear and nonlinear fractional differential equations - Abdulaziz, O.; Hashim, Ishak; Chowdhury, Md. Sazzad Hossien; Zulkifle, A. K. (Pushpa Publishing House, 2007)
The solutions of linear and nonlinear fractional differential equations (FDEs) are considered in this paper. The Adomian decomposition method (ADM) is applied to obtain exact and approximate solutions of the FDEs. The approximate solutions are in terms of rapidly convergent infinite series with easily computable terms. The accuracy of the approximate decomposition solutions is examined against the quadratic numerical scheme (QNS).